Association Between Constraints Encountered by the Farmers in Adoption of Drip Irrigation System and their Selected Independent Variables - yadav, Krishna; Yadav , J. P.; Yadav , Seema; Asha, Kumari (Indian Journal of Extension Education, 2018)
Rajasthan has largest geographical area having only 1per cent water resources of country. Due to arid and semi-arid  climate i.e. negative moisture index, poor soil quality and traditional agriculture practices, the food security, nutritional  security, Irrigation scenario of Rajasthan is characterized by erratic or /sporadic/scanty rainfall, dwindling ground water  resources increasing alternative demand of municipal and industrial sector that means less water available for agriculture.  In Rajasthan, Water is the most precious natural resource, vitally important for agricultural development and for day-to day living..In the changing agricultural scenario world over and shift towards precision farming, drip irrigation happens to  be the technology capable of providing more efficient utilization of water. The study was conducted in eight selected  Gram Panchayat of Jhotwara Panchayat Samiti of Jaipur District of Rajasthan. Two villages were selected from each  selected Gram Panchayat of Jhotwara Panchayat Samiti having maximum number of drip irrigation sets. Thus, sixteen  villages were selected purposively. Ninety six farmers were selected from sixteen selected villages on the basis of  proportional allocation to the size of sample. The seven variables viz.socio-economic status, caste, occupation, education  level, size of land holding, age and extension participation were identified as the important variables to measure the  association between the constraints encountered by the farmers in adoption of drip irrigation system and selected  independent variables and following results were found. It was observed that 'socio-economic status', 'caste', and  'education level' were found to be negative and significantly where as 'occupation' and 'extension participation' were  positive and significantly associated with the constraints encountered by the farmers in adoption of drip irrigation system  while the variables like 'size of land holding' was negative and 'age' was positive but both were non-significantly  associated with the constraints encountered by the farmers in adoption of drip irrigation system.